Luminescence phenomena of carbon dots derived from citric acid and urea – a molecular insight. Issue 29 (12th July 2018) - Kasprzyk, Wiktor; Świergosz, Tomasz; Bednarz, Szczepan; Walas, Karolina; Bashmakova, Natalia V.; Bogdał, Dariusz
Abstract : Elucidation of the molecular origins of the green and blue fluorescence of CDs derived from citric acid and urea. Abstract : In this report, we present the results of our investigations into the elucidation of the chemical structure of moieties responsible for the blue and green luminescence of CDs derived from the microwave-assisted pyrolysis of citric acid in the presence of urea. The molecular fluorophore that forms during the synthesis of green fluorescing CDs is 4-hydroxy-1 H -pyrrolo[3, 4- c ]pyridine-1, 3, 6(2 H, 5 H )-trione (HPPT).